Low carbon air transport development trends and policy implications based on a scientometrics-based data analysis system. (June 2021) - Qiu, Rui; Hou, Shuhua; Meng, Zhiyi
Abstract: There has been increasing attention on low carbon air transport in recent years due to the environmental impact of air transport. To accelerate low carbon air transport development, various efforts have been made. This study analyzes low carbon air transport development trends using a scientometrics-based data analysis system that evaluates all relevant scientific papers, and explores policy implications. From extensive research on low carbon air transport, literature mining and cluster analysis are conducted to obtain a clear definition for low carbon air transport development trends. Cluster, timeline, and timezone visualizations are used to explore development trends for low carbon air transport with some key topics. The innovation and sustainability for low carbon air transport are evaluated, and then some policy implications are proposed for further development, including properly integrating existing policies, formulating auxiliary policies, and developing forward-looking policies. Examining low carbon air transport based on the analysis system involves a precise observation of air transport development trends and provides policy implications, which could be extended to other transport fields requiring emissions reduction. Highlights: Development trends of low carbon air transport are analyzed. Scientometrics-based data analysis system is used to identify and review studies. Policy implications are provided to promote low carbon air transport deveopment Existing policies, auxiliary policies, and forward-looking policies are considered.